Wholesalers and the transformation of Myanmar's maize value chains - Belton, Ben; Cho, Ame; Hall, Michael; Minten, Bart; Reardon, Thomas (Wiley, 2025)
Wholesalers of agricultural crops have historically received limited attention in the literature on agricultural development, which has a strongly productivist focus. When wholesalers are considered, they are often framed as exploitative, taking advantage of information asymmetries, market failures, and unequal power relations to extract heavy surpluses from farmers. However, there is a growing appreciation that wholesalers may play important roles in facilitating agricultural development and rural transformation. This paper evaluates wholesaler conduct and performance using a survey of 218 maize wholesalers in 12 of the major maize-growing and trading townships of South Shan State, Myanmar and the cities of Lashio and Muse in North Shan. Hybrid maize emerged very rapidly in Myanmar over the past two decades to become a major cash crop, supplying domestic animal feed mills and becoming one of Myanmar's most important exports to China and Thailand. Wholesalers have been central to the development of this supply chain and the sector. Contrary to recent literature from Myanmar that has cast maize wholesalers as exploitative, the survey finds that the rapidly growing wholesaler segment of the maize value chain is highly competitive, rapidly changing with respect to technology, and functions efficiently. Farmers obtaining maize inputs from wholesalers in the form of tied output credit sell their maize at prevailing market rates. The emergence of clusters of maize wholesalers and allied actors such as third-party logistics services occurred spontaneously and symbiotically with the expansion of hybrid maize cultivation, and with each set of actors essential to the emergence of the others.